2007
DOI: 10.1002/app.27349
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐viscoelastic behavior of PCNF‐filled polypropylene nanocomposites

Abstract: Thermal and viscoelastic properties of composites of polypropylene (PP) filled with 0-8 vol % of vapor grown platelet carbon nanofibers (PCNF) were investigated. High shear mixing was used to disperse and distribute the nanofibers. Scanning electron microscope (SEM) was used to study the morphology of the composites that indicated the good dispersion of nanofibers within the PP matrix. Thermogravimetric analysis showed thermal stability enhancements due to the presence of PCNF in the PP matrix. DSC analysis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 49 publications
3
18
1
Order By: Relevance
“…The calculated degree of crystallinity of the PP phase increased with increasing content of both nanoparticles, indicating that the nanofillers nucleated the crystallization process. (Frormann et al, 2008) This implies that the existence of nanoparticles facilitates the crystallization of PP and this effect becomes more evident with higher nanoparticle content (Zhao & Li, 2006). Similar results for PP/CaCO3 nanocomposites, PP/carbon nanotube composites and PP/nanoclay composites (Han & Fina , 2011;Frormann et al, 2008;Vakili et al, 2011) have been reported.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 70%
See 4 more Smart Citations
“…The calculated degree of crystallinity of the PP phase increased with increasing content of both nanoparticles, indicating that the nanofillers nucleated the crystallization process. (Frormann et al, 2008) This implies that the existence of nanoparticles facilitates the crystallization of PP and this effect becomes more evident with higher nanoparticle content (Zhao & Li, 2006). Similar results for PP/CaCO3 nanocomposites, PP/carbon nanotube composites and PP/nanoclay composites (Han & Fina , 2011;Frormann et al, 2008;Vakili et al, 2011) have been reported.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 70%
“…(Frormann et al, 2008) This implies that the existence of nanoparticles facilitates the crystallization of PP and this effect becomes more evident with higher nanoparticle content (Zhao & Li, 2006). Similar results for PP/CaCO3 nanocomposites, PP/carbon nanotube composites and PP/nanoclay composites (Han & Fina , 2011;Frormann et al, 2008;Vakili et al, 2011) have been reported. However there are some contradicting results in the literature (Zhao & Li, 2006 Table 3.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 70%
See 3 more Smart Citations